Targeting claudin‐overexpressing thyroid and lung cancer by modified Clostridium perfringens enterotoxin. Issue 2 (8th January 2020) - Piontek, Anna; Eichner, Miriam; Zwanziger, Denise; Beier, Laura‐Sophie; Protze, Jonas; Walther, Wolfgang; Theurer, Sarah; Schmid, Kurt Werner; Führer‐Sakel, Dagmar; Piontek, Jörg; Krause, Gerd
Abstract : Clostridium perfringens enterotoxin (CPE) can be used to eliminate carcinoma cells that overexpress on their cell surface CPE receptors – a subset of claudins (e.g., Cldn3 and Cldn4). However, CPE cannot target tumors expressing solely CPE‐insensitive claudins (such as Cldn1 and Cldn5). To overcome this limitation, structure‐guided modifications were used to generate CPE variants that can strongly bind to Cldn1, Cldn2 and/or Cldn5, while maintaining the ability to bind Cldn3 and Cldn4. This enabled (a) targeting of the most frequent endocrine malignancy, namely, Cldn1‐overexpressing thyroid cancer, and (b) improved targeting of the most common cancer type worldwide, non‐small‐cell lung cancer (NSCLC), which is characterized by high expression of several claudins, including Cldn1 and Cldn5. Different CPE variants, including the novel mutant CPE‐Mut3 (S231R/S313H), were applied on thyroid cancer (K1 cells) and NSCLC (PC‐9 cells) models. In vitro, CPE‐Mut3, but not CPEwt, showed Cldn1‐dependent binding and cytotoxicity toward K1 cells. For PC‐9 cells, CPE‐Mut3 improved claudin‐dependent cytotoxic targeting, when compared to CPEwt . In vivo, intratumoral injection of CPE‐Mut3 in xenograft models bearing K1 or PC‐9 tumors induced necrosis and reduced the growth of both tumor types. Thus, directed modification of CPE enables eradication of tumor entities that cannot be targeted by CPEwt, for instance, Cldn1‐overexpressing thyroid cancer by using the novel CPE‐Mut3. Abstract : Clostridium perfringens enterotoxin (CPE) is used to target carcinomas overexpressing a claudin subset serving as CPE receptors. CPE‐based pores in membrane cause cell death. Structure‐guided CPE modifications (CPE‐S231R/S313H) enabled also claudin‐1 binding and growth reduction of claudin‐1‐expressing papillary thyroid carcinoma (mouse xenotransplants) that could not be targeted by CPEwt. Furthermore, CPE‐S231R/S313H improved targeting of lung cancer (NSCLC) expressing multiple claudins.